The beetle tree of life reveals that Coleoptera survived end‐Permian mass extinction to diversify during the Cretaceous terrestrial revolution. (6th July 2015) - MCKENNA, DUANE D.; WILD, ALEXANDER L.; KANDA, KOJUN; BELLAMY, CHARLES L.; BEUTEL, ROLF G.; CATERINO, MICHAEL S.; FARNUM, CHARLES W.; HAWKS, DAVID C.; IVIE, MICHAEL A.; JAMESON, MARY LIZ; LESCHEN, RICHARD A. B.; MARVALDI, ADRIANA E.; et al.
Abstract Here we present a phylogeny of beetles (Insecta: Coleoptera) based on DNA sequence data from eight nuclear genes, including six single‐copy nuclear protein‐coding genes, for 367 species representing 172 of 183 extant families. Our results refine existing knowledge of relationships among major groups of beetles. Strepsiptera was confirmed as sister to Coleoptera and each of the suborders of Coleoptera was recovered as monophyletic. Interrelationships among the suborders, namely Polyphaga (Adephaga (Archostemata, Myxophaga)), in our study differ from previous studies. Adephaga comprised two clades corresponding to Hydradephaga and Geadephaga. The series and superfamilies of Polyphaga were mostly monophyletic. The traditional Cucujoidea were recovered in three distantly related clades. Lymexyloidea was recovered within Tenebrionoidea. Several of the series and superfamilies of Polyphaga received moderate to maximal clade support in most analyses, for example Buprestoidea, Chrysomeloidea, Coccinelloidea, Cucujiformia, Curculionoidea, Dascilloidea, Elateroidea, Histeroidea and Hydrophiloidea. However, many of the relationships within Polyphaga lacked compatible resolution under maximum‐likelihood and Bayesian inference, and/or lacked consistently strong nodal support. Overall, we recovered slightly younger estimated divergence times than previous studies for most groups of beetles. The ordinal split between Coleoptera and Strepsiptera was estimated to have occurred in the Early Permian. Crown Coleoptera appeared in the Late Permian, and only one or two lineages survived the end‐Permian mass extinction, with stem group representatives of all four suborders appearing by the end of the Triassic. The basal split in Polyphaga was estimated to have occurred in the Triassic, with the stem groups of most series and superfamilies originating during the Triassic or Jurassic. Most extant families of beetles were estimated to have Cretaceous origins. Overall, Coleoptera experienced an increase in diversification rate compared to the rest of Neuropteroidea. Furthermore, 10 family‐level clades, all in suborder Polyphaga, were identified as having experienced significant increases in diversification rate. These include most beetle species with phytophagous habits, but also several groups not typically or primarily associated with plants. Most of these groups originated in the Cretaceous, which is also when a majority of the most species‐rich beetle families first appeared. An additional 12 clades showed evidence for significant decreases in diversification rate. These clades are species‐poor in the Modern fauna, but collectively exhibit diverse trophic habits. The apparent success of beetles, as measured by species numbers, may result from their associations with widespread and diverse substrates – especially plants, but also including fungi, wood and leaf litter – but what facilitated these associations in the first place or has allowed these associations to flourish likely varies within and between lineages. Our results provide a uniquely well‐resolved temporal and phylogenetic framework for studying patterns of innovation and diversification in Coleoptera, and a foundation for further sampling and resolution of the beetle tree of life.